PENGARUH PERSEPSI MAHASISWA AKUNTANSI TERHADAP SISTEM INFORMASI AKUNTANSI DAN E-COMMERCE DALAM PENGAMBILAN KEPUTUSAN BERWIRAUSAHA - Sapulette, Shella Gilby; Anakotta, Fanny Monica; Rooy, Melinda Victoria (LPPM Universitas Bina Bangsa, 2023)
This study aims to empirically test the influence of e-commerce, and accounting information systems and e-commerce on student decision making for entrepreneurship. The independent variables in this study are accounting information systems and e-commerce. While the dependent variable is student decision making for entrepreneurship. This research is quantitative research. This research data was obtained from a research questionnaire. The population in this study were Accounting Department Students in 2018, 2019, and 2020 Faculty of Economics and Business, Pattimura University. The sample selected was 100 respondents using the convenience sampling method which refers to the Slovin formula. The data analysis technique is using multiple linear regression analysis analyzed through the SPSS 26 program. The results of this study show that Accounting Information Systems have a positive significant effect on student decision making for entrepreneurship and e-commerce has a positive and significant effect on student decision making for entrepreneurship